Uma imagem entre as veredas do grande sertão: Diadorim e a construção da androginia - Teixeira, Rafhael Peixoto (2016)
This dissertation has as its objective the mapping of the constructions around the image of androgyny for Diadorim, character in João Guimarães Rosa’s novel Grande Sertão: Veredas(1956). To reflect on Rosa’s work it is necessary to have an attentive look to the diversity of references and all the possible openings in the text, given through language. Starting from the relation between the idea of androgyny and the various passages that demonstrate the composition of the character Diadorim, this research is based on critical / literary studies connected to language, the idea of the third bank in Rosa’s work and the concepts of androgyny and landscape, such as Coutinho (1993), Faria (2007), Finazzi- Agró(2001) and others. This study is justified by the fact that it is able to enhance the discussion field around Rosa’s work and reflect on gender representation in the social imaginary, composed of a binary vision of the world.